Le webdocumentaire : un outil numérique innovant au service de l’enseignement, de la recherche et de la valorisation - Alexandre Klein (Humanités Numériques)
Among the multiplicity of digital tools now available to researchers, the Web documentary stands out by the richness of its possible uses. Fundamentally interactive, this medium combining text, pictures, video, sound, and animation allows to broadcast knowledge online in an accessible and participative way. It appears as an excellent tool to present and valorise research work (especially historical work) as well as to hand down its content and results to a large and various public. Being based on a complex architecture with multiple levels of presentation and different ways of access, it offers a complete freedom of navigation to its users and so asserts itself as a valued pedagogical medium. That is what this paper wants to demonstrate by presenting a published historical Web documentary, entitled Alfred Binet. Naissance de la psychologie scientifique, and another one still in progress about the history of psychiatric nursing in Quebec. Starting from these two concrete examples, we aim to show how this new digital tool enables to reinvent pedagogical and scientific perspectives by offering new technical possibilities and by inviting us to think together research, teaching and valorisation.